Interior Batik Gallery Using Normal Mapping For Virtual Reality - Padmasari, Ayung Candra; Christyowidiasmoro, Christyowidiasmoro; Hariadi, Mochamad (Institut Teknologi Sepuluh Nopember, 2014)
We present an 3D Modelling object for batik Gallery in virtual reality with textured material photo, Lighting effect and primitive mess with Normal Mapping Metthod. Normal Mapping is one of many method to give depht Impression texture and detail for object without many polycount, so we can get efficiency of the computer work without loss of detail desired. in this research we try to explain several techniques in making batik Gallery design textures with modeling 3D, The methods include stage Normal Mapping, Environment maps, bump maps, and shadow maps. The next proscess we can use Directional Light and Point Light for each object to get the impression of depth and real dimension for each texture. The result of this research is to improve the modern batik consept and patterns with immersive 3D Room in Virtual reality